Removal of 2, 4 - dichlorophenol in a sequential anaerobic hybrid reactor - submerged aerobic fixed film reactor system. - I. H. Farooqi (School of Industrial Technology, Universiti Sains Malaysia, 2014)
The purpose of this study was to determine the biodegradability of 2,4-dichlorophenol (2,4-DCP) in an anaerobic reactor aerobic sequential reactor system. Target compound 2,4-DCP present in simulated wastewater at a concentration of 200 mg L-1 was treated sequentially in continuous mode by combined anaerobic hybrid reactor (AHR) and submerged aerobic fixed film (SAFF) reactor . Sodium acetate was used as co-substrate at 3 g L-1. Hydraulic retention time (HRT) was kept constant at 24 h. Almost complete mineralization of 2,4-DCP was achieved at 2,4 DCP loading rates from 0.005 g L-1 d·1 to 0.200 g L-1 d·1 and organic loading rates in AHR from 1.34 kg COD m-d.1 to 1.52 kg COD m-3 d-1. The COD removal efficiency of AHR varied from 50.6% to 70.45%. The 2,4-DCP removal efficiency of AHR varied from 40.3% to 73,6%. The COD removal efficiency of SAFF reactor varied from 85% to 96.9%. The 2,4-DCP removal efficiency of SAFF reactor varied from 83.9% to 100%. The overall COD removal efficiency by combined AHR and SAFF reactor was 92.9% to 98.8%. The overall 2,4-DCP removal efficiency by combined AHR and SAFF reactor was 96% to 100%.